The Noetics of Nature : Environmental Philosophy and the Holy Beauty of the Visible - Foltz, Bruce V. (Book collections on Project MUSE., 2014)
"Both philosophical and theological texts of antiquity argued that a "noetic" or contemplative understanding of nature is higher than the discursive rationality oriented toward domination and control. Studying poets, mystics, and nature writers, this book argues that restoring a sacred view of nature is urgently needed in Western thought"--